Relationship between circadian syndrome and stroke: A cross-sectional study of the national health and nutrition examination survey - Wang, Yuling; Yang, Ling; Zhang, Yan; Liu, Junyan (Frontiers in Neurology, 2022)
Aim: The aim of this study was to assess the relationship of circadian syndrome and stroke. Methods: We performed a cross-sectional analysis of 11,855 participants from the National Health and Nutrition Examination Survey (NHANES) database between 2005-2018, and collected the baseline characteristics. Multivariate logistic regression models were developed to explore the association between circadian syndrome and stroke. Simultaneously, subgroup analyses based on the difference of gender, race and components associated with circadian syndrome also were performed. The odds ratio (OR) and 95% confidence interval (CI) were calculated in the present study. Results: All participants were divided into the non-stroke group and stroke group.There were approximately 3.48% exclusively stroke patients and 19.03% exclusively circadian syndrome patients in our study. The results suggested that the risk of stroke in patients with circadian syndrome was higher than that in patients without circadian syndrome (OR=1.322, 95CI%:1.020-1.713). Similar associations were found in female with circadian syndrome (OR=1.515, 95CI%:1.086-2.114), non-Hispanic whites with circadian syndrome (OR=1.544, 95CI%:1.124-2.122), participants with circadian syndrome who had elevated waist circumference (OR=1.395, 95CI%:1.070-1.819) or short sleep (OR=1.763, 95CI%:1.033-3.009). Conclusion: Circadian syndrome was associated with the risk of stroke. Particularly, we should pay more close attention to the risk of stroke in those populations who were female, non-Hispanic whites, had the symptoms of elevated waist circumference or short sleep.